Detection of cartilage matrix degradation by autofluorescence lifetime. - Manning, H; Nickdel, M; Yamamoto, K; Lagarto, J; Kelly, D; Talbot, C; Kennedy, G; Dudhia, J; Lever, J; Dunsby, C; French, P; Itoh, Y (2013)
Cartilage is a vital organ to maintain joint function. Upon arthritis, proteolytic enzymes initiate degradation of cartilage extracellular matrix (ECM) resulting in eventual loss of joint function. However, there are only limited ways of non-invasively monitoring early chemical changes in cartilage matrix. Here we report that the autofluorescence decay profiles of cartilage tissue are significantly affected by proteolytic degradation of cartilage ECM and can be characterised by measurements of the autofluorescence lifetime (AFL). A compact multidimensional fluorometer coupled to a fibre-optic probe was developed for single point measurements of AFL and applied to cartilage that was treated with different proteinases. Upon treating cartilage with bacterial collagenase, trypsin or matrix metalloproteinase 1, a significant dose and time dependent decrease of AFL was observed. Our data suggest that AFL of cartilage tissue is a potential non-invasive readout to monitor cartilage matrix integrity that may contribute to future diagnosis of cartilage defects as well as monitoring the efficacy of anti-joint therapeutic agents.